Dampak Media Sosial terhadap Etika Pergaulan Anak Muda di Kota Medan - Tarigan, Kevinta; Syahputra, Dedi (Universitas Medan Area, 2025)
This study aims to analyze the impact of social media on the behavior of young people in Medan City. With the increasing use of social media among young people, it is important to understand whether social media has a positive or negative impact on their mindset, social interactions, and behaviors. This study uses a quantitative approach with a sample of 70 respondents from the Medan Baru District area. The data was collected through a questionnaire distributed to young people aged 15 to 25 years old who actively use social media. Data analysis uses descriptive statistics and linear regression tests to determine the relationship between social media use and changes in young people's behavior. The results showed that there was a significant relationship between the frequency of social media use and changes in the social behavior of young people, with several negative tendencies such as reduced direct social interaction and increased anxiety levels.